Satisfaction with continuity of care from the perspective of older adults who are primary care users and its association with depressive symptoms in Santiago, Chile - Moreno, Ximena; Cornejo, Natalia (Frontiers in Medicine, 2025)
Continuity of care is a fundamental component of integrated care for older adults. Previous research suggests that continuity of care predicts a range of health outcomes in this population and is associated with improved detection and reduction of depressive symptoms. This study aimed to estimate satisfaction with continuity of care among primary care users in Chile and to assess whether satisfaction was associated with a positive screen for depression. Data were collected through face-to-face interviews with 247 community-dwelling older adults enrolled in primary care in Santiago, Chile. Continuity of care and depressive symptoms were measured with the Primary Care Assessment Tool and the 9-item Patient Health Questionnaire, respectively. Linear regression models were used to examine the association between a positive screen for depression and continuity of care, adjusting for sociodemographic characteristics and health status. The mean score for continuity of care was 5.00 (SD = 1.61). A positive screen for depression was independently associated with lower satisfaction with continuity of care (β = −0.94, 95% CI −1.56 to −0.32). Financial hardship (β = −0.50, 95% CI −0.91 to −0.08) and risk of social isolation (β = −0.46, 95% CI −0.88 to −0.05) were also associated with lower satisfaction. The complexity of health needs experienced by older adults, driven by mental health conditions, social and economic vulnerabilities, and multimorbidity, underscores the importance of advancing the implementation of an integrated care model for older adults in primary care in Chile.